2013
DOI: 10.1007/s00018-013-1279-3
|View full text |Cite
|
Sign up to set email alerts
|

Brain homeostasis: VEGF receptor 1 and 2—two unequal brothers in mind

Abstract: Vascular endothelial growth factors (VEGFs), initially thought to act specifically on the vascular system, exert trophic effects on neural cells during development and adulthood. Therefore, the VEGF system serves as a promising therapeutic target for brain pathologies, but its simultaneous action on vascular cells paves the way for harmful side effects. To circumvent these deleterious effects, many studies have aimed to clarify whether VEGFs directly affect neural cells or if the effects are mediated secondari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 188 publications
(288 reference statements)
0
42
0
Order By: Relevance
“…Within adult CNS tissues the receptor VEGFR2 is seen in neurones of human, rat and primate brain [4,24,27,39,41], in oligodendroglial progenitors [19], in human microglia [12] and in human spinal neurones [6]. VEGFR2 has also been observed within VSMC, in small arteries of human spinal cord [6] and in blood vessels of peripheral tissues [8,36,37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Within adult CNS tissues the receptor VEGFR2 is seen in neurones of human, rat and primate brain [4,24,27,39,41], in oligodendroglial progenitors [19], in human microglia [12] and in human spinal neurones [6]. VEGFR2 has also been observed within VSMC, in small arteries of human spinal cord [6] and in blood vessels of peripheral tissues [8,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by our finding that endothelial VEGFR2 was not widespread. Physiological effects of VEGFR2 in adult brain include migration of neuronal progenitor and oligodendrocyte progenitor cells [19,41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 In the central nervous system, VEGF not only exerts its effect on the vascular system, but also helps to maintain the neural homeostasis and neural development. 17 VEGF is upregulated during various pathological events in the central nervous system, including ischemia, 18 cold lesions, spinal cord injuries, brain contusion and direct wounding. 19 It has also been reported that VEGF had a neuroprotective role in spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%